The Influence of Work Discipline on Teacher Performance at Harapan Baru III State Elementary School, Bekasi City - Mulyanti, Kurniawati; Partimah, Partimah; Fa'uzobihi, Fa'uzobihi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to determine and analyze the effect of work discipline on teacher performance. The research method used in this research is quantitative and in data collection using a questionnaire. The population in this study consisted of 32 teachers at SD Negeri Harapan Baru III Kota Bekasi. In this study, the entire population was used as a sample. The results of this research hypothesis test are as follows: 1) obtained the significance value of the effect of work discipline (X) on teacher performance (Y) of 0,000 (0,000 < 0,05) and the tcount value of (5,897) > ttable (2,042) which means that work discipline affects teacher performance; 2) obtained a correlation coefficient R of 0,733, which if interpreted in the interpretation table shows that there is a strong relationship between work discipline and teacher performance; 3) then in the determination coefficient table shows the R squared number of 0,537 or 53,7% which can be concluded that work discipline has an influence on teacher performance, while the remaining 46,3% is explained by other variables outside the variables used in this study. Based on the results of the data analysis, it is concluded that there is a significant influence between work discipline on teacher performance at SD Negeri Harapan Baru III Kota Bekasi.